Does therapy with biological drugs influence COVID‐19 infection? Observational monocentric prevalence study on the clinical and epidemiological data of psoriatic patients treated with biological drugs or with topical drugs alone. Issue 6 (17th November 2020) - Brazzelli, Valeria; Isoletta, Eugenio; Barak, Oren; Barruscotti, Stefania; Vassallo, Camilla; Giorgini, Chiara; Michelerio, Andrea; Tomasini, Carlo Francesco; Musella, Valeria; Klersy, Catherine
Abstract: Since the onset of the coronavirus disease 2019 (COVID‐19) pandemic, there has been an open debate on the impact of biological drugs used in the treatment of psoriasis. To define whether patients under treatment with biologics suffer from increased morbidity and mortality from COVID‐19, compared to psoriatic patients treated only with topical drugs, we designed an observational monocentric prevalence study recording the personal and clinical data of psoriatic patients, with focus on the presentation of signs and symptoms related to COVID‐19 in the period of time ranging from 1 January 2020 to 31 May 2020. A total of 180 patients were enrolled into two groups: 100 patients in the topical therapy group and 80 patients in the biological therapy group. No statistically significant difference was found between the groups regarding the prevalence of COVID‐19 infection and symptoms at a bivariable analysis with adjustment for confounders. In conclusion, psoriatic patients under treatment with biologics do not seem to be more susceptible to COVID‐19 compared to other psoriatic patients and we suggest not interrupting treatment with biological drugs, even in areas suffering from active outbreaks of the disease.